Allele-specific methylation of type 1 diabetes susceptibility genes. (May 2018) - Kindt, Alida S.D.; Fuerst, Rainer W.; Knoop, Jan; Laimighofer, Michael; Telieps, Tanja; Hippich, Markus; Woerheide, Maria A.; Wahl, Simone; Wilson, Rory; Sedlmeier, Eva-Maria; Hommel, Angela; Todd, John A.; et al.
Abstract: The susceptibility to autoimmune diseases is influenced by genes encoding major histocompatibility complex (MHC) proteins. By examining the epigenetic methylation maps of cord blood samples, we found marked differences in the methylation status of CpG sites within the MHC genes ( cis -metQTLs) between carriers of the type 1 diabetes risk haplotypes HLA-DRB1*03-DQA1*0501-DQB1*0201 (DR3-DQ2) and HLA-DRB1*04-DQA1*0301-DQB1*0302 (DR4-DQ8). These differences were found in children and adults, and were accompanied by reduced HLA-DR protein expression in immune cells with the HLA-DR3-DQ2 haplotype. Extensive cis -metQTLs were identified in all 45 immune and non-immune type 1 diabetes susceptibility genes analyzed in this study. We observed and validated a novel association between the methylation status of CpG sites within the LDHC gene and the development of insulin autoantibodies in early childhood in children who are carriers of the highest type 1 diabetes risk genotype. Functionally relevant epigenetic changes in susceptibility genes may represent therapeutic targets for type 1 diabetes. Highlights: Marked and persistent differential DNA methylation associated with HLA class II. Carriers of HLA DR3/DQ2 have reduced HLA class II RNA and protein expression. cis -metQTL observed in all type 1 diabetes susceptibility genetic regions. Novel association of differential methylation of LDHC gene with early autoimmunity.